Long-term vegetation monitoring data (1961-2013) from moorland burning plots established at Hard Hill, Moor House in 1954 ... - Rose, R.J.; Marrs, R.H.; O'Reilly, J.; Furness, M. (NERC Environmental Information Data Centre, 2018)
The dataset consists of long-term vegetation monitoring data from the Hard Hill burning plots sited in the Moor House - Upper Teesdale National Nature Reserve, Cumbria. An experiment to investigate the effects of rotational burning and grazing was initiated in 1954, consisting of a replicated block layout. Initial vegetation recording was carried out in 1961 and 1965 using a quadrat method and DOMIN scale. In 1972 onwards, vegetation was recorded using a pin frame. Data were recorded by staff from the Centre for Ecology & Hydrology and its predecessors. ... : Data were recorded by trained botanists employed by the Centre for Ecology & Hydrology and its predecessors. Data were recorded on paper in the field and later digitised. ...